Perancangan Bisnis Udang Crispy dan Sambal Bawang Ebisiji Sebagai Oleh-Oleh Asli Surabaya - Sharon Anindhita; Ferryanto Chia (Universitas Ciputra Surabaya, 2017)
The activity of buying “oleh-oleh” or food souvenir has become a strong Indonesian culture, regardless of someone’s social economic status. However, due to the fact that almost all food souvenir products look similar, along with the increasing activity of urban population, this activity has turned into something rather dull and meaningless. Based on this fact, comes an idea to utilize an original recipe for crispy fried shrimp to be a food souvenir product that appeals to Indonesia’s urban population who fall under the upper-middle and lower-middle class, particularly those who travels regularly. This research was conducted to understand customers’ response to Ebisiji crispy fried shrimp and “sambal bawang”, along with their response related to the activity of buying “oleh-oleh”. The process consists of several phase, including observation, interview, questionnaire, production test, market test, and collecting feedback. All data are obtained through field studies (primary) and literature reviews (secondary), by applying both quantitative and qualitative research method. The researcher then concludes that by making some adaptive changes into the business model, Ebisiji can become a viable solution for the problem stated above.